VARIATIONS OF EVALUATION METHODS IN ONLINE LEARNING: ALTERNATIVE SOLUTIONS AND REFLECTIONS - Bashith, Abdul; Adji, Waluyo Satrio (Proceeding of International Conference on Islamic Education (ICIED), 2022)
COVID-19 brings various changes in the pattern of life, including in the world of education. Evaluation in learning activities carried out various adjustments following the development of the conditions of learning implementation. In online learning during the pandemic, several alternative variations of effective learning methods to do include: test-based evaluation, oral-based evaluation, portfolio-based evaluation, practice-based evaluation, self-assessment-based evaluation, and project-based evaluation. The results of the reflection on the implementation of evaluation in online learning include: difficulty in determining the form of learning evaluation, difficulty in mapping indicators of learning achievement, and difficulty in applying honesty values